Oyster Care: An Innovative Palliative Approach towards SPMI Patients - Decorte, Ilse; Verfaillie, Françoise; Moureau, Loïc; Meynendonckx, Sandrine; Van Ballaer, Kim; De Geest, Isabelle; Liégeois, Axel (Frontiers in Psychiatry, 2020)
Oyster Care is the result of the search by caregivers in Flanders, Belgium, to develop quality care for patients with a Severe and Persistent Mental Illness (SPMI). This article offers a conceptual analysis of the Oyster Care model, based on experiences, analysis, and reflection of the authors, and on several examples. The starting point of the development of this new care model is the complex and difficult context of the care for SPMI patients. Their needs and suffering are very challenging on account of a wide variety of causes. At the same time they are in danger of being neglected by the care system. Paradoxically, the development and implementation of psychosocial rehabilitation in Belgian mental health care puts the care for these patients under pressure. In practice, they are often exposed to over- or under-treatment. Another aspect that has influenced the search for more qualitative care in cases of severe psychological suffering in general and palliative approaches in particular is the background of the legal regulation of euthanasia in Belgium. Oyster Care is an innovative form of the palliative approach and philosophy, tailored to the specific target group of SPMI patients. The caregivers create an “exoskeleton” or “shell” in which SPMI patients can “come to life”: they are mainly dependent on the “external structure” they receive in order to function, rather than on the “internal structure” of their abilities. It is a dynamic approach that responds to the needs, possibilities and pace of each patient: within this safety, people can fold back or take new steps. Oyster Care is also a holistic care approach, based on four pillars: physical care adequately responding to the somatic impairments of these patients; psychological care changing the scope of therapy by focusing on mental comfort and wellbeing; social care providing a structure of daily activities and contacts; existential care enhancing the experience of life as valuable and meaningful. The wellbeing of patients is paramount and requires a range of interventions, such as a highly personal approach, a flexible dealing with rules, a great dose of creativity in everyday life, extensive expertise in somatic care, and specific attention to existential needs and the search for meaning. The development of this care model in a number of care units in Flanders increases the wellbeing of the patients and creates a significant positive dynamic among caregivers. However, more research and resources are needed to further develop and integrate this model.